Occupational Conditions Associated With Negative Mental Health Outcomes in New York State Health Professionals During the COVID-19 Pandemic. Issue 7 (16th July 2022) - Cheslack-Postava, Keely; Bresnahan, Michaeline; Ryan, Megan; Musa, George J.; Amsel, Lawrence; DiMaggio, Charles; Andrews, Howard F.; Susser, Ezra; Li, Guohua; Abramson, David M.; Lang, Barbara H.; Hoven, Christina W.
Abstract : These findings identify circumstances in the occupational settings of healthcare workers most associated with increased odds of adverse mental health outcomes. These may provide specific targets for potential modifications in these settings to reduce the risks to the mental health of these providers during a pandemic. Abstract : Objective: The aim of this study was to assess occupational circumstances associated with adverse mental health among health care workers during the COVID-19 pandemic. Methods: A cross-sectional study examined responses to an on-line survey conducted among 2076 licensed health care workers during the first pandemic peak. Mental health (depression, anxiety, stress, and anger) was examined as a multivariate outcome for association with COVID-related occupational experiences. Results: Odds of negative mental health were increased among those who worked directly with patients while sick themselves (adjusted odds ratio, 2.29; 95% confidence interval, 1.71–3.08) and were independently associated with working more hours than usual in the past 2 weeks, having family/friends who died due to COVID-19, having COVID-19 symptoms, and facing insufficiencies in personal protective equipment/other shortages. Conclusions: Occupational circumstances were associated with adverse mental health outcomes among health care workers during the COVID-19 pandemic, and some are potentially modifiable.